ECONOMIC LAW STUDY ON VILLAGE FUND MANAGEMENT FROM THE PERSPECTIVE OF EFFICIENCY AND TRANSPARENCY - Abdullah, LOD; Pratiwi, ET (Jurnal Multidisipliner Bharasumba, 2025)
Since the enactment of Law No. 6 of 2014 on Villages, the Indonesian government has placed significant emphasis on village development through the allocation of Village Funds. However, its management still faces various challenges, both in terms of regulation and implementation. This study aims to analyze the economic law perspective on Village Fund management in terms of efficiency and transparency and to formulate an ideal concept. The research method used is normative juridical. The findings indicate: (1) The economic law analysis of Village Fund management includes its juridical basis, efficiency from an economic law perspective, transparency as a principle of state financial governance, and the ideal construction of economic law; (2) The ideal concept of Village Fund management requires result-oriented and budget-efficient regulations, transparency as a community right, a strengthened sanction system to ensure compliance, and regulatory reconstruction to make law an active instrument in supporting village welfare. Through an economic law approach, the weaknesses of the current legal system can be addressed, enabling Village Funds to become an effective and equitable development instrument.